EKSEKUSI LELANG HAK TANGGUNGAN TERHADAP KREDIT MACET DI BANK NAGARI PUSAT PADANG - Yudha Prasetyanov; Niko Kasinda (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Banks occupy a very important place in meeting the needs of the community.This can be seen from one of its goals,to satisfy credit needs,the descriptions in this journal are: 1) What are the causes ofbad loans at Bank Nagari.2) How is the execution mechanism of the mortgage auction as a settlement ofbad loans at Bank Nagari.3) What are the obstaclesandefforts made by the Bank towardstheauction execution mechanism as a settlementwith badcredit.To answer these problems, the writer conducted a descriptive sociological juridical research which was conducted to obtain primary data through interviews and the results obtained were presented descriptively. From the results of the research that the author conducted at Bank Nagari central Padang, it can be seen that: 1) The causes of the emergence of bad loans come from internal factors (creditors) andexternal factors (debtors)whichbothhave an important influence on credit. 2) The procedure for the auction execution mechanism at Bank Nagari through KP2LN which has the authority to execute the auction.3) The obstacles commonly encountered by the Bank in the execution of the auction are the price agreement which is dropped below the market price of the collateral, which causes the debtor whose credit is bad to feel loss.Keywords: Agreement, Execution, Auction, Mortgage, Bad Credit